Anemômetro Baseado no Método de Tempo de Trânsito: Estudo comparativo de arquiteturas, avaliação de incertezas e implementação. - Almeida, Will Ribamar Mendes (2004)
Anemometers are instruments, simply, for measuring the velocity of fluids and, in some cases, its direction. Particularly, the measurement of the air velocity extends to applications like: windmills, wind tunnels, electricity generation from Aeolian energy and meteorology. Among the most used methods for the wind velocity determination, the method based on the transit time of ultrasonic waves is stressed for being more suitable to the measurement of the velocity of gases, and which is based on the time required for an ultrasonic wave emitted from a transmitter to reach a receptor. Among the techniques for implementing the transit time the Difference of Time (DT) and Difference of Phase (DP) are emphasized, and both are addressed ins this work. A comparative study, with experimental verification, between the two techniques (DT and DP) is presented in this work, using techniques for compensating the effects of temperature variation on the sound velocity. It was taken into consideration the implementation of the measurement circuits and the propagation of uncertainties with respect to the variables that interfere in the measurement process. From the analyses carried out, the most suitable method for measuring the wind velocity was chosen, and a prototype was developed based on this method. The most suitable method is the Difference of Phase, because the observed uncertainty, in both simulations and experiments, was much smaller than for the DT method.